Production of a human milk oligosaccharide 2′-fucosyllactose by metabolically engineered Saccharomyces cerevisiae - Yu, Sora; Liu, Jing-Jing; Yun, Eun Ju; Kwak, Suryang; Kim, Kyoung Heon; Jin, Yong-Su (Microbial cell factories, 2018)
2'-Fucosyllactose (2-FL), one of the most abundant oligosaccharides in human milk, has potential applications in foods due to its health benefits such as the selective promotion of bifidobacterial growth and the inhibition of pathogenic microbial binding to the human gut. Owing to the limited amounts of 2-FL in human milk, alternative microbial production of 2-FL is considered promising. To date, microbial production of 2-FL has been studied mostly in Escherichia coli. In this study, 2-FL was produced alternatively by using a yeast Saccharomyces cerevisiae, which may have advantages over E. coli. Fucose and lactose were used as the substrates for the salvage pathway which was constructed with fkp coding for a bifunctional enzyme exhibiting L-fucokinase and guanosine 5'-diphosphate-L-fucose phosphorylase activities, fucT2 coding for α-1,2-fucosyltransferase, and LAC12 coding for lactose permease. Production of 2-FL by the resulting engineered yeast was verified by mass spectrometry. 2-FL titers of 92 and 503 mg/L were achieved from 48-h batch fermentation and 120-h fed-batch fermentation fed with ethanol as a carbon source, respectively. This is the first report on 2-FL production by using yeast S. cerevisiae. These results suggest that S. cerevisiae can be considered as a host engineered for producing 2-FL via the salvage pathway.